Distributed secondary control for proportional power sharing and DC bus voltage restoration in standalone DC microgrid - Phan-Thanh Nguyen; Duc Minh Pham (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
This article proposes a distributed secondary control scheme based on the voltage-shifting method for standalone direct current (DC) microgrids to enforce proportional power-sharing under the imbalance of the feeder line impedances and compensate for the DC bus voltage error caused by the droop control. Secondary control will be implemented on local controllers to increase reliability. A low-bandwidth communication network will also be needed to exchange converters’ information. Using information from the communication network, the reference voltage for the primary control will be adjusted to compensate for the droop control and line impedance influences. The appropriate voltage shifting terms will be determined by the delta iteration method. The proposed control will be evaluated with simulations using PLECS software.